How to Reduce Plastic Waste by Using Social Media Marketing? - Lisdayanti, Annisa; Sinaga, Obsatar; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Environmental problems faced in the world, including in Indonesia, are plastic waste. It is estimated that in 2050, plastic waste can exceed the number of fish; this can happen if control measures are not immediately taken. Some cities in the world produce large amounts of plastic waste every year. And one type of plastic waste that is commonly found in plastic straws is included in the top five types of plastic waste. In 2017, a movement that aims to arouse public awareness of the environment, especially the movement not to use plastic straws, has been carried out. The same thing was done by social media influencers who claimed to have started leaving plastic straws; this was based on public concerns about the amount of plastic waste in circulation. This research is descriptive and verification, with a sample of 116 from the community in the city of Bandung obtained by means of iteration calculation 3 times. Data analysis was performed using multiple regression. The results of the research partially showed that of the four independent variables studied, it was found that the variable content creation had a greater influence on increasing people's decisions in using non-plastic straws. And the effect simultaneously obtained a value of 83.9%, and the remaining 16.1% is influenced by other variables outside this study.